The Contribution of Pastoral Institutes for an Inculturated and Contextualized Ministry - Steffen, Paul B., SVD (Archīum Ateneo, 2020)
This article focuses on the contribution of pastoral institutes for an inculturated and contextualized ministry in the non-Western local churches. The treated pastoral institutes in Asia, Africa, Latin America, and Oceania have played an outstanding role in implementing the communion ecclesiology of Vatican II in their respective local churches by moving towards an inculturated Christian faith and church and a contextualized Christian and ecclesial praxis. By following the Vatican II appeal to read and scrutinize the signs of the times, they played a catalytic function in the local non-Western churches to evangelize and to develop a meaningful ministry and participatory community approach, not only for ordained ministers but also for the major part of God’s people, the laity.